Предмет: Алгебра,
автор: Valerua2002
Помогите решить пожалуйста. Буду очень благодарна :)
Приложения:
Ответы
Автор ответа:
0
Приводим к общему знаменателю, получаем
((а+4)(а+2)-а(а+6))/а(а+2) = (а^2+2а+4а+8-а^2-6а)/а(а+2) = 8/а(а+2)
((а+4)(а+2)-а(а+6))/а(а+2) = (а^2+2а+4а+8-а^2-6а)/а(а+2) = 8/а(а+2)
Автор ответа:
0
Благодарю)
Автор ответа:
0
(а+6)(а+4)=а(а+6)
а^2+6а+4а+24=а^2+6а
10а-6а=-24
4а=-24
а=-6
а^2+6а+4а+24=а^2+6а
10а-6а=-24
4а=-24
а=-6
Похожие вопросы
Предмет: Информатика,
автор: naziknusrat
Предмет: Математика,
автор: artemsinkevic232
Предмет: Немецкий язык,
автор: Xykis
Предмет: География,
автор: mnovikova24